PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE MAKE A MATCH TERHADAP HASIL BELAJAR KEWIRAUSAHAAN SISWA KELAS X PEMASARAN - Ningrum Ningrum; Lilian Mega Puri (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
Based on the results of preliminary observations of entrepreneurial values at SMK Muhammadiyah 1 Seputih Banyak class X students still have many learning outcomes that have not reached the minimum completeness criteria (KKM). The learning outcomes of students who have not completed with the number of students are 17 percentages 56.07%, who achieve learning completeness and are categorized as complete with the number of students 13 percentages 43.33%, while the minimum completeness value (KKM) class X marketing SMK Muhammadiyah 1 Seputih Banyak In entrepreneurship lessons is 75. Alternatives to improve student learning outcomes are used the cooperative learning model type make a match, in connection with this problem the formulation of the problem is: